Corporate Social Responsibility: A Conceptualization Based On Organizational Literature - Zenisek, Thomas J. (Academy of Management Review, 1979)
Several definitions and models of the phenomenon of corporate social responsibility are reviewed. These conceptualizations and definitions are found to lack either empirical and/or theoretical support; they have not provided a basis for a clear understanding of the phenomenon. They have, in fact, led to confusion in the literature. I propose a definition of social responsibility based on the notion of a “fit” between the two components of a “business ethic” and societal expectations of the private economic sector. A typology of social responsibility which incorporates this definition, and which is based on the Blau and Scott “prime beneficiary” and the Emery and Trim “causal texture of organizational environment” typologies is also presented.